2016
DOI: 10.1007/s11356-016-7294-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of environmental quality of two estuaries in Ilha do Maranhão, Brazil, using histological and genotoxic biomarkers in Centropomus undecimalis (Pisces, Centropomidae)

Abstract: Estuaries are subjected to continual environmental impacts from activities in the catchment areas. This research assessed the quality of two estuarine habitats located in Ilha do Maranhão, Brazil, through histological and genotoxic biomarkers in Centropomus undecimalis, comparing the data obtained to metal, physical, and chemical concentrations of water samples. The gill histological alterations were analyzed by the histological alteration index and genotoxic lesions in erythrocytes were detected by the Micron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 68 publications
0
5
1
2
Order By: Relevance
“…Epithelial lifting is characterized by the elevation of a continuous epithelium lamina covering secondary lamellae away from the pillar cell system (Shailaja & D’Silva, 2003; Thophon et al, 2003), distancing the external environment and the arrangement of channels around the blood, compromising gas exchanges, requiring fish to increase respiration rate to compensate for the low oxygen uptake (Cantanhêde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial lifting is characterized by the elevation of a continuous epithelium lamina covering secondary lamellae away from the pillar cell system (Shailaja & D’Silva, 2003; Thophon et al, 2003), distancing the external environment and the arrangement of channels around the blood, compromising gas exchanges, requiring fish to increase respiration rate to compensate for the low oxygen uptake (Cantanhêde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research, Society and Development, v. 9, n. 10, e4119108691, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8691 O C. undecimalis tem sido utilizado como sinalizador de qualidade ambiental em estudos de monitoramento de estuários no estado do Maranhão. Essa espécie é chave nesses estudos em função da sua bieocologia, em especial ao seu hábito carnívoro, migração entre diferentes ecossistemas e sua plasticidade ecológica (Cantanhêde et al, 2016;Pereira et al, 2015).…”
Section: Dietaunclassified
“…(2020) and Weber et al (2020) observed high concentrations of metals, such as Iron (Fe), Aluminum (Al), Manganese (Mn), and Lead (Pb) in the Doce River, even three years after the dam broke. The presence of these metals in aquatic ecosystems can cause negative impacts on exposed organisms, such as genetic and reproductive damage, reduced growth rate and potentially fatal pathologies (Cantanhêde et al 2016, Viana et al 2018. Xenobiotics, such as metals, can act in different pathways in organisms, involving different physiological processes (Tolussi et al 2018), affecting sexual differentiation (Baroiller and Guiguen 2001) and gonadal development (Vested et al 2014), and inducing vitellogenin synthesis in males (Vetillard and Bailhache 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The species of Astyanax genera are relatively small (10-12 cm, as an adult). They move in shoals and being important forage specie to shes in a higher lever of the trophic chain (Pereira et al, 2016). Astyanax lacustris (Lütken 1875) has morphological characteristics that include this species in the group also known as Astyanax bimaculatus.…”
Section: Introductionmentioning
confidence: 99%